Social media as a primary source of information: Exploring its role in disseminating the current situation in Palestine - Maharani, Nadya Ayu Maharani (Gema Wiralodra, 2024)
The proliferation of social media has changed the global information paradigm, enabling immediate and direct access to breaking news. This research examines the role of social media as a primary source of information, focusing on the context of the conflict in Palestine. Through a qualitative desk research approach, it explores how social media contributes to disseminating current events in Palestine. The analysis involved a review of literature related to social media development, conflict information dynamics, and its impact on public opinion. The results show that social media has become an essential tool in accelerating and expanding the reach of information about the situation in Palestine. Individual actions, such as sharing news or personal views, can trigger significant public responses and shape narratives that influence global perceptions. Moreover, the active engagement of social media users in relaying actual information plays a key role in shaping opinions and attitudes toward the conflict. This research provides insight into the complex dynamics of social media as a key source of information, illustrating how information is disseminated and understood in the context of the Palestinian conflict. The implications of this research can contribute to further understanding social media's role in shaping public opinion and influencing the global narrative on sensitive issues such as the Palestinian conflict.